Subclinical Aortic Root Pathology in Close Relatives of Patients with Bicuspid Aortic Valve - Ivaniv Y.; Lozynska N.; Ivaniv I. (Львівський клінічний вісник)
Introduction. Bicuspid aortic valve (BAV) is a widespread structural anomaly of the heart that occurs at a frequency of 0.9-1.5% in the general population. As usual, this feature of the structure of the valve is combined with the expansion of the ascending part of the aorta. However, the degree of dilation of the aorta does not correspond to the severity of the valve function disorder. In many studies, it is emphasized that in persons with BAV the elastic properties of the proximal aorta are significantly reduced. This can be explained by the fact that the genetic defect, through which the BAV is formed, is also responsible for the dilatation of the root of the aorta. The analysis of the pedigree of individuals with BAV indicates the family prevalence of this heart disease with the auto-dominant inheritance of inheritance and reduced penetrance. According to various sources, among the relatives of the first degree (FDR) of affinity the prevalence of BAV is 9.0-21.0%. However, there is no convincing information that would confirm the hereditary nature of the onset of aortic aneurysm in these individuals. If this is true, then even those relatives of persons with BAV who have a normal valve of the aorta of a tricuspid structure should have some hidden signs of pathology of the aortic root that are not clinically detected, but in the case of acute or chronic hemodynamic overload (for example, arterial hypertension ) can cause aneurysm of the aorta or even its dissection. Aim. To find out whether close relatives of patients with bicuspid aortic BAV with aortic valve of the normal tricuspid formulation have hidden changes in the ascending aortic region based on studying its diameter at different levels and elastic properties of the aorta, both in patients with BAV and their FDRs with the normal aortic valve, comparing the appropriate parameters with the control. Materials and methods. The study included 36 adults (14 women, 22 men) aged 18 to 56 years old with BAV who underwent echocardiographic examination during 2009-2013. In addition, their FDRs were invited to a survey, of which 68 individuals (28 women, 40 men aged 18-62). Of these, 8 patients (12.0%) also had BAV. So, the aortic root diameters on four levels and distensibility index have been examined in 44 patients with BAV, their 60 FDRs with normal aortic valve and 40 healthy subjects. Results. It was revealed that FDRs have significantly bigger indexed diameter of aortic annulus in comparison with the controls (1.740 ± 0.031 сm/m VS 1.600 ± 0.019 сm/m) and diameter of sinuses of Valsalva (2.780 ± 0.019 cm/m VS 2.200 ± 0.018 сm/m). Also both FDRs and BAV s have significantly lower aortic distensibility (1.28 ± 0.26 and 1.47 ± 0.31 mm Hg•10–3) than the controls (3.32 ± 0.29 mm Hg•10–3). Conclusions. So, the aortic root in FDRs of patients with BAV is wider and demonstrates functional abnormality with potential pathological meaning in a future.